Preparation of self‐healing acrylic copolymer composite coatings for application in protection of paper cultural relics - Xu, Jicheng; Zhang, Tao; Jiang, Yan; Yang, Dongya; Qiu, Fengxian; Chen, Qian; Yu, Zongping (Polymer engineering and science, 2020)
Due to the limitation of storage condition, paper cultural relics are constantly subject to human damage and natural aging, requiring rescue protection. In this study, a series of nanocellulose/calcium carbonate microcapsule/fluorine‐acrylamide styrene/acrylic copolymer composite protection materials were prepared and used as an efficient self‐healing composite coating for paper cultural relics protection. CaCO3 microcapsules were prepared by interfacial reaction method and doped into the polymer materials to obtain the self‐healing composite coating. The properties of composite protection materials were studied via the self‐healing experiment, dry heat accelerated aging test, and reversible experiment. The effects of composite protection materials on simulate paper cultural relics were analyzed. The results show that when the amount of hollow calcium carbonate microcapsules was 0.500 g, the composite protection materials had good comprehensive performances. The prepared materials work positive influence on the conservation of simulate paper cultural relics that could be one of the potential materials for application in protection of paper cultural relics. POLYM. ENG. SCI., 60: 288–296, 2019. © 2019 Society of Plastics Engineers